Butyl benzyl phthalate promotes prostate cancer cell proliferation through miR-34a downregulation. (February 2019) - Zhu, Mingming; Wu, Jieshu; Ma, Xiao; Huang, Cong; Wu, Rui; Zhu, Weiwei; Li, Xiaoting; Liang, Zhaofeng; Deng, Feifei; Zhu, Jianyun; Xie, Wei; Yang, Xue; et al.
Abstract: Prostate cancer is the most common malignancy in men. Phthalate esters are a class of environmental endocrine disruptors and were reported to be cancer promoting agents, however the potential role of phthalate esters in prostate cancer has been rarely reported. Mounting evidence has shown that miR-34a is a master tumor suppressor miRNA in cancer. The aim of this study was to investigate the role of butyl benzyl phthalate (BBP), one of the typical phthalate esters, in cell proliferation of prostate cancer cells. Human prostate cancer LNCaP and PC-3 cells were exposed to low dose of BBP for 6 days. The results showed that 10 −6 and 10 −7  mol/L BBP increased the expression of cyclinD1 and PCNA, decreased p21 expression, and induced cell growth in both LNCaP and PC-3 cells. Furthermore, we found that BBP significantly downregulated the expression of miR-34a, along with upregulation of miR-34a target gene c-myc. Using cell tranfection of miR-34a mimic and inhibitor, we demonstrated that BBP promoted cell proliferation through miR-34a/c-myc axis in prostate cancer cells. Findings from this study could provide new insight into the involvement and the molecular mechanism of phthalate esters on prostate cancer. Highlights: BBP promoted the proliferation of prostate cancer cells. BBP altered the expression of cell cycle genes of prostate cancer cells. BBP downregualted miR-34a in prostate cancer cells. miR-34a inhibited the proliferation of prostate cancer cells. BBP promoted cell proliferation through miR-34a/c-myc axis in prostate cancer cells.